Anxiety and self-belongingness of inclusive learners: the stance, facet overcoming - G., Panneerselvam; Wiselet S., Bella (Institute of Advanced Engineering and Science, 2025)
It was inevitable that young learners at this time would have to pay special attention to both prosaic life and their schoolwork. It is also acknowledged that the majority of learners live in a multi varied situations. This study focuses on and analyses academic anxiety and self-belongingness in learners in an inclusive setup. Academic anxiety is related to distinct characteristic of learner, including gender, venue, instructional media, and family structure. The study focused on these four personal characteristics, and an experimental design technique was used to perform the analysis. This was accomplished using a convenience sampling procedure, which yielded 284 samples. The descriptive analysis is assisted to examine the collected data. However, there is a significant variance regarding their locality of residency. As a result, there is an essential geographical divide between them. The study outcomes also revealed a correlation between learners’ academic concerns and sense of belonging. Significant differences in personnel parameters, such as the residential location of learners, were observed.